Karakter Morfologi Necrobia spp. (Coleoptera ; Cleridae) Pada Beberapa Jenis Bahan Simpanan - Ni Made Riska Dewi; Jusuf . Manueke; Caroulus S. Rante; Elisabeth R.M. Meray (Universitas Sam Ratulangi, 2013)
ABSTRACTThe morphological and behavioral characters indicate the identity of the type or species of insects and closely related to the selection and determination of the type of insect food. This study aimed to see differences in morphological characters Necrobia spp. on some kinds of deposits. It is hoped this research can provide information on morphological characters Necrobia spp. on some kinds of deposits. This study uses survey methods, and sampling was done by